2016
DOI: 10.1002/pssa.201600387
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational band structure of nanoscale phononic crystals

Abstract: The vibrational properties of two-dimensional phononic crystals are studied with large-scale molecular dynamics simulations and finite element method calculation. The vibrational band structure derived from the molecular dynamics simulations shows the existence of partial acoustic band gaps along the $\Gamma$-M direction. The band structure is in excellent agreement with the results from the finite element model, proving that molecular dynamics simulations can be used to study the vibrational properties of suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Figure 1 shows the polycrystalline configuration as an example for the model systems simulated in this work. The phononic crystal models simulated in this work are similar to the model used in reference [7]. With a size of 2.7 million atoms the models here are, however, smaller than the 9 million atom model used in that article.…”
Section: Computational Detailsmentioning
confidence: 98%
See 1 more Smart Citation
“…Figure 1 shows the polycrystalline configuration as an example for the model systems simulated in this work. The phononic crystal models simulated in this work are similar to the model used in reference [7]. With a size of 2.7 million atoms the models here are, however, smaller than the 9 million atom model used in that article.…”
Section: Computational Detailsmentioning
confidence: 98%
“…To overcome this problem, a previously introduced sampling method was employed which calculates the velocity autocorrelation functions from the velocity data of a subset of the atoms [7]. From each of the configurations, 250,000 atoms were randomly selected and the velocities of these atoms were stored during the simulations every 15 simulations steps.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Ref. [15][16][17][18][19]). Compared to the widely used molecular dynamics programs mentioned in the preceding section, MDNTP is a relatively small code which facilitates the incorporation and testing of new features.…”
Section: Hybrid Parallelizationmentioning
confidence: 99%
“…The existence of low-frequency locally resonant bandgaps (LRBGs) gives rise to the application of locally resonant phononic crystals (LRPCs) in the reduction of low-frequency vibration and noise [3]. However, it has been a challenging task due to the long wavelength and weak attenuation of the low-frequency waves.…”
Section: Introductionmentioning
confidence: 99%
“…Stubbed phononic-crystal plates can be classified into two types: the single-sided stubbed phononic-crystal plate and the doublesided stubbed phononic-crystal plate. The single-sided stubbed phononic-crystal plate [3] consists of a square array of stubs on one side of a homogeneous plate [6]. Subsequently, many researchers investigated the effects of material properties and geometric parameters on the BG of the single-sided stubbed phononic-crystal plate and found that the mass and the geometric parameter effect can help tune the bandgap into low frequencies [8].…”
Section: Introductionmentioning
confidence: 99%